2008
DOI: 10.1590/s1413-73722008000100002
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in energy-tension cycle and self-regulation of mood

Abstract: The theory of mood proposed by Thayer is examined in a sample of Spanish psychology students (N = 176). Results showed the existence of a circadian pattern of energy and tension levels, individual differences, such as gender, circadian type (morningness or eveningness), and some possible cross-cultural differences, though energy levels in American and Spanish samples were similar. Data also indicated differences in the assessment and interpretation of personal problems in relation to mood: according to energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A first probable explanation, based on mood self-regulation and embodiment of the body's energy level by the visual system, could explain the mood influence obtained in Experiment 2. Several studies have shown that participants in a joyful or sad mood make an effort to self-regulate their mood: Those who are sad in order to improve their mood (Garrosa et al, 2008;Isen, 1985;Thayer et al, 1994) and those who are joyful in order to maintain their mood (Wegener & Petty, 1994) or to reach neutrality (Erber & Erber, 2000;Erber & Tesser, 1992;Martin & Tesser, 1996). In a series of 9 experiments, Gailliot et al (2007) showed that self-regulatory effort caused a decrease in the body's energy level (i.e., decrease in blood glucose level).…”
Section: Discussionmentioning
confidence: 99%
“…A first probable explanation, based on mood self-regulation and embodiment of the body's energy level by the visual system, could explain the mood influence obtained in Experiment 2. Several studies have shown that participants in a joyful or sad mood make an effort to self-regulate their mood: Those who are sad in order to improve their mood (Garrosa et al, 2008;Isen, 1985;Thayer et al, 1994) and those who are joyful in order to maintain their mood (Wegener & Petty, 1994) or to reach neutrality (Erber & Erber, 2000;Erber & Tesser, 1992;Martin & Tesser, 1996). In a series of 9 experiments, Gailliot et al (2007) showed that self-regulatory effort caused a decrease in the body's energy level (i.e., decrease in blood glucose level).…”
Section: Discussionmentioning
confidence: 99%
“…Positive affect has been linked to social experiences of eating while isolated consumption has been associated with loneliness and comfort eating (Oxford Economics and the National Centre for Social Research, 2018;Locher et al, 2005). Low mood is also closely linked to low energy and tiredness (Garrosa et al, 2008), prompting food selections to provide 'highs', thereby implicating cravings for foods that stimulate mood activating dopamine neurons of addiction and reward (De Macedo et al, 2016). Active pleasure-seeking behaviours to reduce negative states (Freud, 1920) or avoidance distraction (Spoor et al, 2017) can fuel unconscious and conscious eating patterns to mitigate negative affect, and often involve sweet or fatty products (Evers et al, 2010;Tomiyama et al, 2011).…”
Section: The Effect Of Mood On Dietary Intakementioning
confidence: 99%